Pengaruh Model Pembelajaran Berbasis Masalah Berbantuan Simulation Based Laboratory (SBL) Terhadap Hasil Belajar Fisika Peserta Didik Kelas XI IPA SMAN 1 Montong Gading - Nurhikmah Nurhikmah; Gunawan Gunawan; Syahrial Ayub (Department of Physics Education, Universitas Mataram, 2018)
This research is aimed to know the influence of Problem-Based Learning Models assisted with Simulation Based Laboratory (SBL) on studentsÃ¢â¬â¢ physics learning outcome in class XI IPA of SMAN 1 Montong Gading academic year 2015/2016. The material used in the research is momentum and impulses. The type of the research is quasi experiment with pretest-posttest control group design. The population which is used in this research are the whole students of class XI IPA of SMAN 1 Montong Gading which decided by purposive sampling technique. C lass XI IPA 1 as the experiment class and class XI IPA 2 as the control class. The result of study was analized using t-test polled varians. Based on the research outcome, it can be concluded that Problem-Based Learning Models Assisted with Simulation Based Laboratory (SBL) influenced students` physics learning outcome.